Angelman syndrome: Current and emerging therapies in 2016. Issue 4 (8th November 2016) - Tan, Wen‐Hann; Bird, Lynne M.
Abstract : Angelman syndrome (AS) is a severe neurodevelopmental disorder caused by a loss of the maternally‐inherited UBE3A ; the paternal UBE3A is silenced in neurons by a mechanism involving an antisense transcript ( UBE3A‐AS ) at the unmethylated paternal locus. We reviewed all published information on the clinical trials that have been completed as well as the publicly available information on ongoing trials of therapies in AS. To date, all clinical trials that strove to improve neurodevelopment in AS have been unsuccessful. Attempts at hypermethylating the maternal locus through dietary compounds were ineffective. The results of an 8‐week open‐label trial using minocycline as a matrix metalloproteinase‐9 inhibitor were inconclusive, while a subsequent randomized placebo‐controlled trial suggested that treatment with minocycline for 8 weeks did not result in any neurodevelopmental gains. A 1‐year randomized placebo‐controlled trial using levodopa to alter the phosphorylation of calcium/calmodulin‐dependent kinase II did not lead to any improvement in neurodevelopment. Topoisomerase inhibitors and antisense oligonucleotides are being developed to directly inhibit UBE3A‐AS . Artificial transcription factors are being developed to "super activate" UBE3A or inhibit UBE3A‐AS . Other strategies targeting specific pathways are briefly discussed. We also reviewed the medications that are currently used to treat seizures and sleep disturbances, which are two of the more common complications of AS. © 2016 Wiley Periodicals, Inc.